Analysis of Extreme Rainfall in Padang City Based on The Influence of MJO and IOD in The Period 1991-2020 - Cindy Magriza Putri; Nofi Yendri Sudiar; Hamdi; Letmi Dwiridal (Journal of Experimental and Applied Physics, 2023)
Rainfall above normal can be categorized as extreme rainfall. Extreme rainfall can be caused by various factors, such as global, local, and regional factors. Some regional factors that influence rainfall are the Madden Julian Oscillation (MJO) and the Indian Ocean Dipole (IOD). Padang City has high rainfall intensity which can result in extreme rainfall. The lack of adequate disaster mitigation results in flood disasters when extreme rainfall occurs. Therefore, this research aims to determine normal rainfall, extreme rainfall trends and the relationship between the MJO and IOD phenomena with the frequency of extreme rainfall in Padang City. This information is needed for future disaster mitigation planning. The method used is the time series method and statistical correlation test. Based on the results of the analysis, it is known that Padang City is an area with an equatorial rain type, where the highest rainfall occurs in November with a value of 512 mm and the lowest in May with a value of 268 mm. The trend in extreme rainfall tends to decrease with regression coefficient values ​​of 0.0412 and 0.0708. There is a significant relationship between the number of negative IOD events and the frequency of extreme rainfall with a correlation coefficient of 0.483 and 0.403 which indicates a moderate correlation. There is no significant correlation between the number of strong MJO events in Phases 3 and 4 and the frequency of extreme rainfall, with a correlation coefficient of -0.038 – 0.105.